The Content of Organic Materials in the Sediment and Abundance of Macrozoobenthos in Kampar River Estuary Teluk Meranti Pelalawan Riau Province - Tomi Suhendra; Syahril Nedi; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in June 2015 in the estuary of Kampar River of Teluk Meranti Pelalawan Riau Province. The purpose of this study was to determine the content of organic materials in sediments and abundance of macrozoobenthos. The method used in this study was a survey method. The stations was determined based on a purposive sampling which consisted of 3 stations, and each station was divided into 5 plots. The results showed that the sediment in the estuary of Teluk Meranti was dominated by sandy mud with organic materials content ranging from 1.15 to 2.08%. There were two classes of Macrozoobenthos found, Bivalves and Polychaetes with abundance 46-70 ind/m2. Its diversity index (H') was low, but high in term of dominance index (C). The uniformity index value (E) showed that species spread unevenly. The relationship between organic content and abundance of macrozoobenthos indicates an intermediate correlation with Y = 90,326-21,95x (r = 0.41, R2 = 0.1696). It seems that abundance of Macrozoobenthos in this area was more influenced by other environmental factors.Key words : Organics materials, abundance, macrozoobenthos, Teluk Meranti